The family Leucospidae (Hymenoptera: Chalcidoidea) from the South of Saudi Arabia, with the first report of the genus Micrapion and description of Leucospis arabica sp. nov. Issue 31 (26th August 2018) - Gadallah, Neveen S.; Soliman, Ahmed M.; Abu El-Ghiet, Usama M.; Elsheikh, Tarek Y.; Al Dhafer, Hathal M.
ABSTRACT: The family Leucospidae (Hymenoptera: Chalcidoidea) from Saudi Arabia is reviewed. Specimens were mainly collected from the south-western region of the country – Raydah (Abha, Asir), Sajid (Farasan Islands, Jazan) and Wadi Tourabah (Mandaq, Al Baha); and from Egypt – Wadi Khoshb (Sinai Peninsula), as well as a specimen ( Leucospis elegans Klug) deposited in the Efflatoun Bey collection, Cairo University, Egypt. The genus Micrapion Kriechbaumer is here recorded for the first time from the fauna of the Arabian Peninsula, with a single species, M. clavaforme. Leucospis arabica Gadallah and Soliman sp. nov. ( dorsigera group) is described. Leucospis africana ( elegans group) is also newly recorded from the Saudi Arabian fauna, in addition to L. elegans which has been previously recorded. An illustrated key and a list of all leucospid species recorded and expected to occur in Saudi Arabia are provided. www.zoobank.org/lsid:Zoobank.org:pub:40BEF37F-0D92-4AEF-9990-30C1CFC3A7A7